PLANNING OF THEORETICAL AND PRACTICAL TRAINING IN ORGANIZING THE EDUCATION PROCESS OF FUTURE ENGINEERS - Sattorova Mahliyo Burxanovna (Journals Park Publishing, 2022)
This article discusses theoretical and practical training of future engineers in the organization of the educational process, their importance in planning and managing the educational process.
Keywords: Education, technology, consciousness, professional education, educational process